Real-time study on the effect of dust accumulation on performance of solar PV panels in Malaysia - Sulaiman, S.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
Solar photovoltaic (PV) systems is a promising method of generating electrical power from renewable energy in Malaysia. However, light obstruction on the solar panel due to dust accumulation can significantly influence the performance and efficiency of the system, and thus can affect the cash flow of the system operators. Despite the problem, only little studies have been conducted on the nature of dust accumulation on solar PV panels. Many of the studies involved imitation of dust for in laboratory tests, which could not assess the actual phenomenon. The main objective of this work was to study the effect of dust accumulation on the performance of solar PV panel in Malaysia. This work would enable appropriate scheduling for cleaning of the panels. The study was conducted on real-time basis on a building's roof. Measurements of irradiation, power output and the corresponding mass of dust collected were performed on hourly, daily, weekly and monthly basis. It was found from the study that the system's performance could drop by about 6 annually. On the maintenance aspect, in order to sustain economical operation, the cleaning interval should be every two months for industrial-scale systems that produce a minimum of 100 MWh/day. The interval would be shorter (i.e. one month) for smaller systems (residential). Â© 2015 IEEE.